Neuregulin-1 (NRG-1) mRNA and protein in the adult human brain. - Law, A; Shannon Weickert, C; Hyde, T; Kleinman, J; Harrison, P (2004)
Neuregulin-1 (NRG-1) plays important roles in the development and plasticity of the brain, and it has recently been identified as a susceptibility gene for schizophrenia. Though there are rodent data, little is known about its distribution in the human brain. The aim of this study was to ascertain the localization of NRG-1 and its mRNA in multiple regions of the normal adult human brain. We investigated NRG-1 mRNA in 11 subjects using in situ hybridization and northern analysis, and NRG-1 protein in six subjects using immunohistochemistry and Western blotting. NRG-1 mRNA was present as bands of approximately 2, 3 and 6 kb. It was clearly detected in the prefrontal cortex (middle laminae), hippocampal formation (except CA1), cerebellum, oculomotor nucleus, superior colliculus, red nucleus and substantia nigra pars compacta. At the cellular level, NRG1 mRNA was abundant in hippocampal and cortical pyramidal neurons and some interneurons, and in cerebellar Purkinje cells and Golgi cells. NRG-1 protein was detected as bands of approximately 140, 110, 95 and 60 kD. Immunohistochemistry revealed NRG-1 in many cell populations, consistent with the mRNA data, being prominent in pyramidal neurons, Purkinje cells, several brainstem nuclei, and white matter neurons. Moderate NRG-1 immunoreactivity was also observed in cerebellar and dentate gyrus granule cells, and some glia. Within neurons, NRG-1 staining was primarily somatodendritic; in the cell body staining was granular, with clustering close to the plasma and nuclear membranes. There was also labeling of some fiber tracts, and local areas of neuropil (e.g. in the dentate nucleus) suggestive of a pre-synaptic location of NRG-1. The data show a widespread expression of NRG-1 in the adult human brain, including, but not limited to, brain areas and cell populations implicated in schizophrenia. Using these normative data, future studies can ascertain whether the role of NRG-1 in the disease is mediated, or accompanied, via alterations in its expression.